2022
DOI: 10.1111/joa.13634
|View full text |Cite
|
Sign up to set email alerts
|

Structure and regulation of desmosomes in intercalated discs: Lessons from epithelia

Abstract: For electromechanical coupling of cardiomyocytes, intercalated discs (ICDs) are pivotal as highly specialized intercellular contact areas. ICD consists of adhesive contacts, such as desmosomes and adherens junctions (AJs) that are partially intermingled and thereby form an area composita to provide mechanical strength, as well as gap junctions (GJ) and sodium channels for excitation propagation. In contrast, in epithelia, mixed junctions with features of desmosomes and AJs are regarded as transitory primarily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 113 publications
1
27
0
Order By: Relevance
“…However, to our knowledge in cardiomyocytes this complex was not known before. It has been very well demonstrated that desmosomes in the epithelia or ICDs in the cardiomyocytes not only provide cellular cohesion but can also be part of a signaling hub (Broussard et al, 2015, Najor et al, 2017, Muller et al, 2021, Yeruva and Waschke, 2022), thus disrupting EGFR signaling in this context might lead to changes at the desmosome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to our knowledge in cardiomyocytes this complex was not known before. It has been very well demonstrated that desmosomes in the epithelia or ICDs in the cardiomyocytes not only provide cellular cohesion but can also be part of a signaling hub (Broussard et al, 2015, Najor et al, 2017, Muller et al, 2021, Yeruva and Waschke, 2022), thus disrupting EGFR signaling in this context might lead to changes at the desmosome.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is increasing evidence that desmosomes not only provide cellular cohesion, but also act as signaling hubs (Waschke, 2019, Muller et al, 2021), meaning that desmosomes can influence, but are also influenced by cellular signaling processes. Recent advancement in research suggests that similar molecular mechanisms are present in AC and pemphigus, an autoimmune skin disease, as well as inflammatory bowel diseases (Waschke, 2019, Shoykhet et al, 2020, Schmitt and Waschke, 2021, Yeruva and Waschke, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, ADAM10 inhibition shifted keratinocyte adhesion towards a hyperadhesive state, which is suggested to be required for keratinocytes and cardiomyocytes to acquire a very strong adhesive state in order to resist a high mechanical stress and probably reduce susceptibility for diseases ( 38 , 49 , 50 ). This is in line with the finding that ADAM10 is more active at high Ca 2+ ( 23 , 28 ).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Mutations in Dsg2 and Dsc2 are known to cause arrhythmogenic right ventricular cardiomyopathy whereas those in Pg and Dp cause cardiomyopathy as well as various cardio-cutaneous syndromes (62)(63)(64)(65). Some aspects in the pathophysiology of arrhythmogenic right ventricular cardiomyopathy may be similar to pemphigus due to common aspects in the structure and regulation of desmosomal contacts in cardiac intercalated discs and desmosomes of the epidermis (66). Moreover, mutations in desmosomal proteins have been shown to affect skin appendages.…”
Section: Other Desmosome-related Diseasesmentioning
confidence: 99%